The Effect of Heat Treatment on the Machinability, Tensile Strength, Hardness, Ductility and Microstructure of Carbon steel (GOST 50). (Journal of University of Babylon for Engineering Sciences, 2018)
In this work, the heat treatments were performed by three types of processes: normalizing, quenching and tempering, where the samples were heated to 900°C and held for 1 hour inside the furnace at that temperature. The first group of hot samples was cooled by air to room temperature through the normalizing process, but the second group was rapidly cooled by two types of the quenching media: (cold water at 5°C and polymer solution). The samples after quenching processes were tempered by heating to 450°C for one hour as a soaking time at this temperature. The samples were then taken out of the furnace, and cooled by air. The machinability, tensile strength, hardness, ductility and microstructure tests of carbon steel (GOST 50) have been achieved after the completion the heat treatment processes. The results appeared improvement and change in these properties after the heat treatments due to the change of the hardness, ductility and toughness of samples.